" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
f(x) = u . v
u = x² --> u' = 2x
v = cosec² 2x --> v' = 2 . cosec 2x . (- cosec 2x . cotan 2x) 2
= - 4 cosec² 2x . cotan 2x
f'(x) = u'.v + u.v'
f'(x) = 2x . cosec² 2x + x² . (-4 cosec² 2x . cotan 2x)
= 2x . cosec² 2x - x² . cosec² 2x . cotan 2x
= x . cosec² 2x ( 2 - x . cotan 2x)
2) f(x) = x² . cotan² 2x
f(x) = u.v
u = x² --> u' = 2x
v = cotan² 2x --> v' = 2 . cotan 2x. ( - cosec² 2x) . 2
= -4 . cotan 2x . cosec² 2x
f'(x) = u'.v + u.v'
f(x) = 2x . cotan² 2x + x² . ( -4 . cotan 2x . cosec² 2x)
= 2x . cotan² 2x - 4x² . cotan 2x . cosec² 2x
= 2x . cotan 2x ( cotan 2x - 2x . cosec² 2x)
semoga membantu ya :)